Thrombocytopenia in Klebsiella pneumoniae liver abscess: a retrospective study on its correlation with disease severity and potential causes - Chen, Lulu; Wang, Hongguang; Wang, Hairui; Guo, Yawen; Chang, Zhihui (Frontiers in Cellular and Infection Microbiology, 2024)
Objective: Thrombocytopenia is commonly associated with infectious diseases and serves as an indicator of disease severity. However, reports on its manifestation in conjunction with Klebsiella pneumoniae liver abscess (KPLA) are scarce. The present study sought to elucidate the correlation between thrombocytopenia and KPLA severity and delve into the etiological factors contributing to the incidence of thrombocytopenia.Materials and Methods: A retrospective analysis of the clinical data from patients with KPLA admitted between June 2012 and June 2023 was performed. Baseline characteristics, biochemical assessments, therapeutic interventions, complications, and clinical outcomes were compared between patients with and without thrombocytopenia. To investigate the potential etiologies underlying thrombocytopenia, the association between platelet count reduction and hepatic venous thromboembolism was examined, with a particular focus on platelet consumption. Furthermore, bone marrow aspiration results were evaluated to assess platelet production anomalies.Results: A total of 361 KPLA patients were included in the study, among whom 60 (17%) had concurrent thrombocytopenia. Those in the thrombocytopenia group exhibited significantly higher rates of thrombophlebitis (p = 0.042), extrahepatic metastatic infection (p = 0.01), septic shock (p = 0.024), admissions to the intensive care unit (p = 0.002), and in-hospital mortality (p = 0.045). Multivariate analysis revealed that thrombocytopenia (odds ratio, 2.125; 95% confidence interval, 1.114-4.056; p = 0.022) was independently associated with thrombophlebitis. Among the thrombocytopenic patients, eight underwent bone marrow aspiration, and six (75%) had impaired medullar platelet production. After treatment, 88.6% of thrombocytopenic patients (n = 47) demonstrated recovery in their platelet counts with a median recovery time of five days (interquartile range, 3-6 days).Conclusions: Thrombocytopenia in patients with KPLA is indicative of increased disease severity. The underlying etiologies for thrombocytopenia may include impaired platelet production within the bone marrow and augmented peripheral platelet consumption as evidenced by the presence of thrombophlebitis.